Performance enhancement of a desiccant evaporative cooling system using direct/indirect evaporative cooler. (March 2015) - Elgendy, E.; Mostafa, A.; Fatouh, M.
Abstract: In this paper, three novel desiccant evaporative cooling system configurations are proposed, simulated and compared with the conventional system under a wide range of ambient air temperature (30: 40 °C) and humidity ratio (0.01: 0.02 kgv  kga −1 ). In configuration-I, a direct/indirect evaporative cooling is inserted before the rotating heat exchanger. However, it is inserted after the rotating heat exchanger for system configuration-II. In configuration-III, an extra direct/indirect evaporative cooling is added in an opposite manner. Validation results confirm that, simulation and experimental results are in a good agreement with average errors of 2.23 and 3.87% for ambient air temperature and humidity ratio, respectively. Energetic analysis revealed that configuration-I has the highest cooling capacity while configuration-III has the highest thermal COP and air handling COP. Exergetic efficiency of config-III is higher than the conventional system with 54% as average value over the range of ambient air humidity. Highlights: Three novel desiccant evaporative cooling configurations are compared energetic and exergetic. The simulation program is validated with the experimental data and achieves a good agreement. Config-III achieves higher exergetic efficiency than the conventional system with 50%. Air handling capacity of config-I is higher than that of the conventional system by 17%. Config-II considers the simplest construction and achieves an increase in system COP by 28%.